Association of Stress-Related Factors With Anxiety Among Chinese Pregnant Participants in an Online Crisis Intervention During COVID-19 Epidemic - Shangguan, Fangfang; Wang, Ruoxi; Quan, Xiao; Zhou, Chenhao; Zhang, Chen; Qian, Wei; Zhou, Yongjie; Liu, Zhengkui; Zhang, Xiang Yang (Frontiers in Psychology, 2021)
Background：Previous systematic review indicated the prevalence of prenatal anxiety as 14% to 54%. Pregnant women are a high-risk population for COVID-19. However the prevalence of anxiety symptoms and related factors is unknown in Chinese pregnant women during COVID-19 outbreak. Objective：To investigate the prevalence of anxiety symptoms and the related factors in Chinese pregnant women who were attending crisis intervention during the COVID-19 pandemic. Methods：The data of this cross-sectional study were collected in about two months (February 28 to April 26, 2020). Data analysis was performed from April to May 2020. Participants completed a set of questionnaires via the Wechat Mini-program before starting the online self-help crisis intervention for COVID-19 epidemic. A total of 2120 Chinese pregnant women who were attending a self-help crisis intervention participated in this study. A survey was developed to address possible stress-related factors in pregnant women during the COVID-19 outbreak, including demographic, socioeconomic and pregnancy-related factors, as well as COVID-19 related factors. Generalized Anxiety Disorder-7 (GAD-7) scale and the 10-item perceived stress scale were respectively employed to measure anxiety and stress-related factors. Results：A total of 21.7% (459) of pregnant women reported at least mild anxiety (≥ 5 on the GAD-7 scale), and only 82 women reported moderate to severe anxiety (≥ 10 on the GAD-7 scale). Factors associated with at least mild anxiety included living in Hubei province (OR = 1.68, 95% CI = 1.32-2.13), nobody providing everyday life support (OR = 1.81, 95% CI = 1.18-2.77), pelvic pain or vaginal bleeding (OR = 1.67, 95% CI = 1.32-2.09), and higher perceived stress (OR = 6.87, 95% CI = 5.42-9.02). Having relatives or neighbors with a diagnosis of COVID-19 was not associated with anxiety (p > 0.05). Conclusions and Relevance：Our findings indicate that evaluation and intervention for maternal and infant health are necessary in pregnant women with anxiety during COVID-19 epidemic, especially those with higher perceived stress, less everyday life support, or vaginal bleeding. Interactions among these related medical, social and psychological factors need to be investigated in future studies.